Listening to the hidden sounds in the forest - Najar-Rodriguez, A.J.; Sapkota, S.; Burgess, S. (New Zealand Plant Protection, 2016)
Many bark beetles (Coleoptera Curculionidae Scolytinae) exhibit a wide array of acoustic abilities including sounds used in mate attraction territoriality and defence In New Zealand the goldenhaired bark beetle Hylurgus ligniperda and the black pine bark beetle Hylastes ater are two species of forest insects which may be found on export logs Acoustic signals have been shown to discourage a related bark beetle the western pine beetle Dendroctonus from entering into pine logs and to disrupt mating and tunnelling These recent studies combined with observations of H ligniperda and H ater helped to establish the concept that acoustic disruption could be used as part of a wider systems approach to deter these beetle species near saw mills skid sites and ports If proven effective this technique would add value to New Zealand log exports and decrease the reliance on toxic fumigants as the primary control measure This study shows some of the functions and physical characteristics of the acoustic signals produced by H ligniperda and H ater